Keep up or drown: adjustment of western Pacific coral reefs to sea-level rise in the 21st century. Issue 7 (July 2015) - van Woesik, R.; Golbuu, Y.; Roff, G.
Abstract : Since the Mid-Holocene, some 5000 years ago, coral reefs in the Pacific Ocean have been vertically constrained by sea level. Contemporary sea-level rise is releasing these constraints, providing accommodation space for vertical reef expansion. Here, we show that Porites microatolls, from reef-flat environments in Palau (western Pacific Ocean), are 'keeping up' with contemporary sea-level rise. Measurements of 570 reef-flat Porites microatolls at 10 locations around Palau revealed recent vertical skeletal extension (78±13 mm) over the last 6–8 years, which is consistent with the timing of the recent increase in sea level. We modelled whether microatoll growth rates will potentially 'keep up' with predicted sea-level rise in the near future, based upon average growth, and assuming a decline in growth for every 1°C increase in temperature. We then compared these estimated extension rates with rates of sea-level rise under four Representative Concentration Pathways (RCPs). Our model suggests that under low–mid RCP scenarios, reef-coral growth will keep up with sea-level rise, but if greenhouse gas concentrations exceed 670 ppm atmospheric CO2 levels and with +2.2°C sea-surface temperature by 2100 (RCP 6.0 W m −2 ), our predictions indicate that Porites microatolls will be unable to keep up with projected rates of sea-level rise in the twenty-first century.